The Use of Cohesive Markers in Reading Passages of The English Textbooks for Primary School Students - Torian Putra; Arono Arono; Wisma Yunita (Journal of Primary Education (JPE), 2026)
This study aimed to identify cohesive markers in English textbooks of the 2013 Revised Curriculum for Grades IV, V, and VI published by the Indonesian Ministry of Education and Culture. The analysis focused on grammatical cohesion (reference, conjunction, substitution, and ellipsis) and lexical cohesion (repetition, hyponymy, synonymy, antonymy, and collocation). Using a content analysis method, 39 reading texts were analyzed (14 from Grade IV, 9 from Grade V, and 16 from Grade VI). The results indicated that: 1) Reference was the most dominant grammatical cohesive marker across all levels; 2) Repetition was the most frequent lexical cohesive marker; 3) Grammatical cohesion overall occurred more frequently than lexical cohesion. Furthermore, while distribution patterns were similar, the variety of markers evolved across grades. However, synonyms were found to be the least utilized markers. In conclusion, the prevalence of these markers suggests that they should be explicitly taught to elementary students to enhance their reading comprehension and mastery of textual meaning.